DuchenneConnect Registry Report - Rangel, Vanessa (Public Library of Science, 2012)
Research activity in Duchenne/Becker muscular dystrophy has surged in recent years, requiring robust information networks to support ongoing development. Established by Parent Project Muscular Dystrophy in late 2007, DuchenneConnect was created to bridge the information gap between care providers, researchers and the patient community, thereby addressing medical care needs and accelerating the pace of therapeutic advancements. This report represents the first in a new series that will be regularly shared by DuchenneConnect and PPMD. Data in this report was collected through June 2011.